Capacity Building of Village Apparatus in Ulapato A Village, Telaga Biru District, Gorontalo Regency - Widya Kurniati Mohi; Muh. Firyal Akbar (Journal of Universal Community Empowerment Provision, 2021)
The purpose of this program is community empowerment action through outreach on the Capacity Building of Village Apparatus in Ulapato A Village, Telaga Biru District, Gorontalo District. This program is carried out as an effort to improve the understanding of the officials in carrying out their duties as service providers and to assist the officials of Ulapato A Village, Telaga Biru District, Gorontalo District in implementing good service in accordance with the duties and functions that are implemented with a qualified capacity. Methods The implementation of this activity is carried out by using the lecture method, through the provision of materials adapted to the abilities and absorption of the apparatus as well as the community. This method is expected to provide knowledge and insights for officials and institutions as well as the community. The results and discussion show that the successful implementation of this community service program can be seen by the enthusiasm of all the stakeholders who were present, namely officials as well as the community. It is suggested to the village government that it is necessary to strengthen human resources within the village government of Ulapato A to be able to improve work quality services. Further improve training and socialization on increasing the capacity of village officials for the achievement of an organization.